Histopathological characteristics of breast tumors at Madani General Hospital Medan - Yunata, Kianie Engaline; Lina, Juliana; Wardhani, Fiska Maya (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2024)
Cytology and histopathology include examinations to diagnose breast tumors. The diagnosis of advanced stages of breast tumors can lead to reduced therapeutic options and success. This study aimed to describe the results of cytological and histopathological examinations of patients with breast tumors at the Anatomical Pathology Laboratory of Madani Medan General Hospital between the period 2018-2022. This study was descriptive and retrospective. The study population included all the medical records of patients diagnosed with breast tumors. The research sample consisted of the medical records of patients with FAM and Carcinoma Mammae obtained by consecutive sampling. The results of cytological and histopathological examinations showed that the majority of breast tumor patients were both aged 17-25 years with a percentage of 42.9% and 52.4%, respectively). The results of the cytological examination showed that the majority of patients had benign tumor diagnoses (85.7%) and histology (90.5%). Malignant tumors were diagnosed based on the results of cytological examination (14.3%) and histology (9.5%). Based on the relationship between age. Based on the relationship between age and diagnosis of benign and malignant tumors, the results of cytological examination showed that patients aged 12-16 years, 17-25 years, and 26-35 years all had benign tumors (100%), patients aged 36-45 years had benign tumors (50.0%) and malignant tumors (50.0%), and patients aged 56-65 years all had malignant tumors (100.0%). Histopathological examination results showed that patients aged 12-16 years, 17-25 years, 26-35 years, and 36-45 years all had benign tumors (100%), patients aged 46-55 years had benign tumors (50.0%) and malignant tumors (50.0%), and patients aged 56-65 years all had malignant tumors (100.0%).